Irrigation in San Marcos: Transition to Bureaucratic Tradition - Lynch, Bárbara D. (1986)
The study of the development of irrigation raises a series of basic questions related to the role played by it in Andean societies. A dominant assumption in much of the past literature on irrigation in Peru suggests that hydraulic arrangements in both semi-arid and arid lands largely determine the nature of the state and of society. Wittfogel's hydraulic hypothesis, expanded, elaborated and applied to Peru by Stewart (1955), became the paradigm elaborated and redefined by a whole generation of intellectuals. For example, Mitchell (1976), considers Quinua (Ayacucho) as an irrigation society and resolves to refute some of Wittfogel's ideas related to centralism and despotism. Even so, Mitchell continues to perceive irrigation as a preponderant factor in the process of social and political formation.